(untitled) (Economic and Political Thought, 2017)
The social Market Economy model functioning in the Federal Republic of Germany is a valuable source of inspiration for numerous states that want to reform their political, social and economic systems. It also constitutes an interesting ‘object’ of research and analyses. The Social Market Economy was initially introduced in the western occupation zones and after the German reunification in 1990 it was extended into the territory of the former German Democratic Republic and, to some extent, it constituted a point of reference for the reforms in the Central European states. The article tries to answer the question to what extent the German experience with the Social Market Economy may be useful for the states undergoing the process of system change, especially in the Eastern European region.